2013
DOI: 10.1097/imi.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Transit Time Flow Measurement in Predicting Graft Patency after Coronary Artery Bypass Grafting

Abstract: Objective Transit time flow measurement (TTFM) is a method used to assess intraoperative blood flow after vascular anastomoses. Angiography represents the criterion standard for the assessment of graft patency after coronary artery bypass grafting (CABG). The purpose of this study was to compare flow measurements from TTFM to diagnostic angiography. Methods From October 9, 2009, to April 30, 2012, a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Although intraoperative assessment of grafts with transit time flow measurement can provide physiologic assessment of bypass grafts and is currently recommended, there may be a greater incidence of false negatives compared with angiography. 2 Postoperative angiographic graft assessment is typically reserved for patients who have a deviation in expected clinical course or have objective evidence of ischemia. In postoperative CABG patients who undergo left heart catheterization for electrocardiogram changes, chest pain, or hemodynamic changes, 69% have a positive finding related to bypass grafts on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although intraoperative assessment of grafts with transit time flow measurement can provide physiologic assessment of bypass grafts and is currently recommended, there may be a greater incidence of false negatives compared with angiography. 2 Postoperative angiographic graft assessment is typically reserved for patients who have a deviation in expected clinical course or have objective evidence of ischemia. In postoperative CABG patients who undergo left heart catheterization for electrocardiogram changes, chest pain, or hemodynamic changes, 69% have a positive finding related to bypass grafts on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This is angiographically seen as a 25-30% shrinking of the graft diameter. Intimal hyperplasia develops each subsequent year and 2% graft occlusion occurs per year [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al found a significant difference in the measured graft flow between patent and nonpatent left IMA-LAD grafts. 26) Six left IMA-LAD grafts with peroperative reduced graft flow of < 15 mL/minute were found to be non-patent at follow-up by Handa et al 27) Lehnert et al found that the graft flow was directly correlated with the follow-up outcomes, with an observed 4% decreased risk of the graft failure for every 1 mL/minute increase in the graft flow. 28) These evidences were in line with the outcomes of the current study.…”
Section: Discussionmentioning
confidence: 99%